2016
DOI: 10.1183/13993003.00647-2015
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel diseases, chronic liver diseases and the lung

Abstract: This review is devoted to the distinct associations of inflammatory bowel diseases (IBD) and chronic liver disorders with chronic airway diseases, namely chronic obstructive pulmonary disease and bronchial asthma, and other chronic respiratory disorders in the adult population. While there is strong evidence for the association of chronic airway diseases with IBD, the data are much weaker for the interplay between lung and liver multimorbidities. The association of IBD, encompassing Crohn's disease and ulcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 144 publications
2
16
0
1
Order By: Relevance
“…Several similarities in the underlying pathological mechanisms have been described and may explain the association between IBD and airway diseases[1,2,22-24]. Dysbiosis and an inappropriate immune response to intestinal microbiota are considered key components of the pathophysiological process in IBD[25].…”
Section: Similarities In Pathogenesis and Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several similarities in the underlying pathological mechanisms have been described and may explain the association between IBD and airway diseases[1,2,22-24]. Dysbiosis and an inappropriate immune response to intestinal microbiota are considered key components of the pathophysiological process in IBD[25].…”
Section: Similarities In Pathogenesis and Risk Factorsmentioning
confidence: 99%
“…Similarly, an immune response to lung microbiota seems to occur in airway diseases such as bronchiectasis[26]. A dysregulation of protease activity is present in both IBD[27] and COPD[28], and is associated with the breakdown of connective tissue components and the ensuing remodeling process[1,29]. Alterations in immune cell homing function[1,22] may explain the low grade chronic systemic inflammation that is present in IBD[30], COPD[31], asthma[32-34] and bronchiectasis[35-38].…”
Section: Similarities In Pathogenesis and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…IBD patients show significantly decreased lung function test outcomes in comparison to healthy controls. In a review including over 600 patients with UC, more than 50% of patients showed abnormal pulmonary function test results when compared to healthy controls, and the decrease in diffusion capacity of the lung for carbon monoxide (DLCO) was the most common defect [3, 4]. …”
Section: Introductionmentioning
confidence: 99%